1996
DOI: 10.1128/iai.64.12.5225-5232.1996
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii protease inhibits Clostridium difficile toxin A effects in the rat ileum

Abstract: Saccharomyces boulardii, a nonpathogenic yeast, is effective in treating some patients with Clostridium difficile diarrhea and colitis. We have previously reported that S. boulardii inhibits rat ileal secretion in response to C. difficile toxin A possibly by releasing a protease that digests the intestinal receptor for this toxin (C. Pothoulakis, C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(118 citation statements)
references
References 38 publications
5
98
0
5
Order By: Relevance
“…reuteri RC14 can be used to improve the effectiveness of certain antibiotics in the treatment for Clostridium difficile secondary infection. While the exact mechanisms remain unknown, many hypotheses have been advanced to explain the antimicrobial activity of probiotics, notably competition for binding sites on the epithelium (Conway et al 1987), decreased intestinal cell permeability (Stratiki et al 2007), competition for nutrients (Sonnenburg et al 2006), degradation of toxin receptors (Castagliuolo et al 1996), stimulating the immune system (Kaila et al 1992) and production of various inhibitory substances such as organic acids (Vandenbergh 1993), bio-surfactants or hydrogen peroxide (Pridmore et al 2008), all previously reviewed (Fliss et al 2011). Secretion of cell signalling compounds such as reutericyclin (G€ anzle 2004) and bacteriocins has also been proposed as an antimicrobial mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…reuteri RC14 can be used to improve the effectiveness of certain antibiotics in the treatment for Clostridium difficile secondary infection. While the exact mechanisms remain unknown, many hypotheses have been advanced to explain the antimicrobial activity of probiotics, notably competition for binding sites on the epithelium (Conway et al 1987), decreased intestinal cell permeability (Stratiki et al 2007), competition for nutrients (Sonnenburg et al 2006), degradation of toxin receptors (Castagliuolo et al 1996), stimulating the immune system (Kaila et al 1992) and production of various inhibitory substances such as organic acids (Vandenbergh 1993), bio-surfactants or hydrogen peroxide (Pridmore et al 2008), all previously reviewed (Fliss et al 2011). Secretion of cell signalling compounds such as reutericyclin (G€ anzle 2004) and bacteriocins has also been proposed as an antimicrobial mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Ileal secretion in response to Cl. difficile toxin A is inhibited by S. boulardii due to proteolysis of the toxin and inhibition of toxin binding to its receptor (Pothoulakis et al 1993;Castagliuolo et al 1996). Moreover, its preventive properties concerning traveller's diarrhoea (Kollaritsch et al 1993), antagonistic effects on Candida species (Ducluzeau and Bensaada 1982) as well as immunostimulatory effects (Caetano et al 1986;Buts et al 1990) have also been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite one died after the C. difficile challenge, the diarrhea symptoms were alleviated in the remaining animals, and a few became normal after re-administration of L. lactis carrying the empty plasmid. Together these observations indicate that the probiotic L. lactis has a protective effect on CDI animal model and may prevent C. difficile-associated diarrhea in animals by inhibiting C. difficile colonization and/or other mechanisms [18,19].…”
Section: Effect Of Recombinant L Lactis Live Vaccine On C Difficilementioning
confidence: 71%